Congenital autosomal recessive cutis laxa 2A - Sonia Karapurkar,; Parag Patel,; Bhumika Mishra,; Arpita Thakkar,; Mona Gajre, (Indian Journal of Child Health, 2021)
Congenital cutis laxa is a rare inherited skin disorder and shows diverse phenotypic features among its different variants. Most forms are progressive and dysmorphic features worsen with age giving an appearance of early ageing. Autosomal recessive cutis laxa, type 2a, (ARCLIIa) is the only variant where phenotypic features undergo spontaneous regression and self-resolution with age. We are reporting a case of congenital ARCLIIa, in a child who had primarily presented with right-sided pneumonia. The child was investigated and worked up for cutis laxa based on skin appearance and characteristic facies (loose sagging skin, redundant skin folds, and hound-like facies). In view of history of a cousin having similar findings which had self-resolved overtime without any treatment, we further suspected it to be type 2A variant, which was proven by genetic analysis (ATP6V02 gene). Hence, we wish to report this case.